Current Collision Mitigation Technologies for Advanced Driver Assistance Systems – A Survey - Hairi Zamzuri; Umar Zakir Abdul Hamid; Konstantin Pushkin; Djahid Gueraiche; Mohd Azizi Abdul Rahman (PERINTIS eJournal, 2021)
Road accidents remain a major cause for fatalities globally. A lot of researches have been done and it is widely reported that vehicle automation can reduce human errors, thus reducing road fatalities. The construction of a fully autonomous vehicle is among the major developments of vehicle automation. Many surveys have been done about vehicle automation and Advanced Driver Assistance Systems (ADAS) is one of the fundamental features of a fully autonomous vehicle. Main ADAS features include Automatic Cruise Control, Automatic Parking, Collision Avoidance as well as Lane Departure Warning systems. In this paper, current advances of collision mitigation technologies for ADAS are reviewed as an introductory idea for researchers and general audiences who are new to this field. Each of the systems are discussed in their own sections. The highlights and future directions for each system are brought to light. Several future work suggestions for a comprehensive ADAS systems are highlighted. As this work is intended as a general survey on ADAS, the technical specifications of each system are not discussed in details.